Mengungkap Keindahan Gerak: Eksplorasi Estetika Dalam Tari Bada Hatam. - Mawar Siswanto; Trianti Nugraheni; Tatang Taryana (Universitas Medan Area, 2025)
Tari Bada Hatam Betawi by Wiwiek Widyastuti is a performing arts piece of high aesthetic value, reflecting the richness of Betawi culture through its unique movements and expressions. This article aims to examine the aesthetics of Tari Bada Hatam Betawi from a philosophical perspective, particularly focusing on the aesthetics of culture and art. This research uses a qualitative descriptive method, involving an in-depth analysis of the movement structure and the dance's meaning. The analysis results indicate that Tari Bada Hatam Betawi is not merely a form of artistic expression but also a means to communicate the philosophical values of Betawi life, such as balance, harmony, and simplicity. Through a semiotic study, it reveals that Tari Bada Hatam is multi-layered. This means the dance not only displays movements and aesthetics but also holds complex and profound symbolic values and meanings. Furthermore, Wiwiek Widyastuti's work reflects the integration of tradition and innovation, making it relevant in the context of contemporary performing arts. This research is expected to contribute to a deeper understanding of Betawi dance aesthetics and the application of a philosophical approach to traditional performing arts.